A study on the Factors Affecting Continuous Usage Intention of Computer Aided Engineering (CAE) Software - Cho, Yongwon; Kim, Dae Sik; Phuong, Huy Tung; Gim, Gwang Yong (2019 20th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2019)
Manufacturing industry is considered to be one of the industrial sectors expected to take the biggest influence while leading the recent changes under the Fourth Industrial Revolution. The product development sector, which is the core to secure the competitiveness of the manufacturing industry, has already advanced considerably to the level of advancement and optimization of highly conflicting subjects such as time, quality and cost. Meanwhile, the manufacturing industry is facing new challenges. Also, unlike ERP, SCM, and CRM, which are representative enterprise solutions for business activities of manufacturing enterprises, the engineering domain represented through product development is a realistic restriction which cannot be sufficiently researched because of the features of engineering expertise, closeness, confidentiality. At this point which we are facing unexperienced challenges, to study on the factors affecting continuous usage intention of Computer Aided Engineering (CAE) software, which is one of the themes to address innovation to different level, covering the conflicting subjects of time, cost and quality is meaningful as basic data for predicting and preparing a direction of change afterward. For this purpose, empirical studies on the affecting factors of perceived value, information system, and brand on satisfaction and continuous use intention of CAE experts in manufacturing companies and government - funded research institutes has been initiated and conducted. The result of this study confirms that perceived economic and time value, information and service quality and brand trust affect continuous usage intention through satisfaction. Through this study, it is confirmed that experts using CAE software at work are fully aware of the economic and temporal benefits of CAE software. It is also confirmed that information quality and service quality that directly affect business results, have a significant relationship with satisfaction and there are still areas to improve for diffusion of CAE software through the rejection of system quality in terms of ease of use. Based on the results, this study proposes a practical implication of CAE software use and academic implication to apply the experience value theory to the new field and provide verification of existing researches under the circumstances of lack of empirical studies on CAE software.